Covid-19 third Wave - Impact on Financial Markets and Economy - Carl Heinz Daube (ZBW - Leibniz Information Centre for Economics, 2021)
The pandemic, caused by Covid-19, has hit the whole world since the beginning of 2020. The current extent of the resulting economic and social upheaval cannot be estimated yet. In this working paper, an attempt to compare Covid-19 figures with the development on the financial markets and the real economy is made. We try to analyse whether significant effects have already occurred and where these could still come with a time lags. – – Die Pandemie, hervorgerufen durch Covid-19, hat seit Anfang 2020 die ganze Welt erfasst. Das tatsächliche Ausmaß der dadurch verursachten wirtschaftlichen und sozialen Verwerfungen sind noch nicht abschätzbar. In diesem Working-Paper wird ein Versuch unternommen, Covid-19 Zahlen der Entwicklung an den Finanzmärkten und der Realwirtschaft gegenüber zu stellen und zu analysieren, wo es bereits zu massiven Auswirkungen gekommen ist und wo diese mit zeitlicher Verzögerung noch kommen könnten.
Keywords: G1; 330; Covid-19; third wave; stock market; economic impact